Academic Challenges and Coping Mechanisms among Senior High School Students with Overseas Filipino Worker Parents - Taola, Mica; Sagdi, Lorence James; Millado, Erwina; Harun, Nurul Ain; Alviar, Jayson (Future Science / FSH-PH Publications, 2024)
Students with Overseas Filipino Worker (OFW) parents face a wide array of challenges that affect their well-being. The consequences of parent’s absence directly affect their child’s psychological state which can result to poor academic performance. This study aimed to determine the academic challenges and coping mechanisms of the Senior High School students with Overseas Filipino Workers (OFWs) parents through analysis of their lived experience. This study employed a phenomenological research design. In this study a purposive sampling technique was employed to select the six (6) respondents with OFW parents in Senior High School. These students were selected using the following criteria: (1) a senior high school student at Tairan National High School; (2) whose mother is working abroad; and (3) willingness of the respondents to participate in the study. The data collected from the interview were analyzed using thematic analysis. Three (3) subthemes emerged in the senior high school students’ academic challenges: (1) school-related problem; (2) lack of parent’s attention and guidance; and (3) communication. On the other hand, the coping mechanisms of the students include (1) reciprocating parent’s efforts; (2) understanding the parents’ reasons for working abroad; (3) building a circle of friends and family support system. Results showed that the parents’ absence affects the academic performances of the students. However, the students displayed strong commitment to do well in school to reciprocate parents’ sacrifices. Thus, this phenomenological study establishes the baseline in developing programs and support system to the students with OFW parents.